Learning Achievement and Self-Regulation Behavior of Nursing Students by Crystal-Based Learning in Nursing Research Subject - ธรรมกุล ดวงเนตร; ชอบอรุณสิทธิ ชญานิศ; ศรีทะแก้ว ณัฐยา (Princess of Naradhiwas University Journal, 2018)
The aims of this pre-posttest quasi–experimental research were to: 1) compare learning achievement before and after using crystal-based learning, 2) compare self-regulation behavior before and during studying by crystal-based learning, and 3) evaluate the crystal-based learning. Sample was third-year nursing students who enrolled in nursing research subject, faculty of nursing, Suan Dusit University. A total of 33 volunteers participated in this study. Experimental instrument was crystal-based learning. Questionnaires about knowledge, and self-regulation behavior, as well as an interview form were used for data collection in order to evaluate the crystal-based learning. The Item-Objective Congruence Index (IOC) was 0.83, 0.87 and 0.89, respectively. Reliability of the questionnaire about knowledge, and self-regulation behavior were 0.62 and 0.90, respectively. Descriptive statistics and paired t–test were employed for data analysis.Results were as follows: 1) After the experiment, nursing students had higher level of learning achievement than before the experiment (M=24.75, S.D.=3.72, and M=21.59, S.D.=2.42, respectively) with statistical significance (p <.01). The nursing students had higher learning achievement after applying the crystal-based learning, 2) Self-regulation behavior score during the experiment was higher than before the experiment (M=88.56, S.D.=6.25, and M=76.84, S.D.=7.90, respectively) with statistical significance (p <.01). The findings of this study indicate that crystal-based learning could facilitate nursing students to achieve their learning outcomes. In addition, the crystal-based learning encouraged a positive attitude towards nursing research subject. Therefore, crystal-based learning should be promoted and applied into other subjects in higher education.